PENGARUH PELAYANAN MANAJEMEN KESISWAAN TERHADAP KEPUASAN SISWA - Aisah Aisah (Universitas Djuanda, 2015)
The purpose of this study was to obtain empirical data on the Influence of Student Management Services to the satisfaction of Elementary School Students in Dayatussalam Cileungsi Bogor. This is quantitative descriptive research type. The place of research was conducted in Bogor Cileungsi Dayatussalam Elementary School. The subjects were students of class IV, V, and VI Elementary School Dayatussalam Cileungsi Bogor. The analysis used include quantitative data analysis. The analysis technique used is a simple regression analysis and correlation coefficient significance test (t-test). Based on the results obtained, there is influence between student affairs management services to the satisfaction of the students in the Elementary SchoolDayatussalam Cileungsi Bogor. The amount of influence that occurs from student management services performed by the Government Elementary School Dayatussalam amounted to 9.2%. Results calculated with simple regression shows the influence of student management services to the satisfaction of the students in the Elementary School Dayatussalam Cileungsi Bogor. Thisis indicated by the line equation is Y = 55.42 + 0.29 X so that once held hypothesis testing using simple regression equation it is known the positive influence among student affairs management services to the satisfaction of the students in the Elementary School Dayatussalam Cileungsi Bogor. Regression coefficient of 0.29 states that any additions (for the sign +) each enhanced service management student, then the student satisfaction will also increase by 0.29. Influence occurs a positive influence so that students become more increased satisfaction. The conclusion is evident from the results of the calculation of the frequency distribution table of data management services and student satisfaction student who is fair.